A coincidental finding: Type I intestinal malrotation in an adult initially diagnosed by ultrasound - (:unkn) unknown (My University, 1997)
Embryologic failure of rotation of the midgut around the superior mesenteric artery results in intestinal malrotation. Although most of these malrotations give symptoms in the neonatal period, they can be seen in adulthood. We describe a case in which color Doppler study showed superior mesenteric vein on the left of superior mesenteric artery during an investigation of hematemesis and abdominal pain, with a type 1 malrotation. We believe that position of superior mesenteric artery and vein should be carefully checked during routine US examinations, as this can be the first clue of missed malrotation.
Keywords: Adult; Doppler US; Intestinal malrotation; US